2013
DOI: 10.1056/nejmoa1110404
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antifungal Therapy for Cryptococcal Meningitis

Abstract: BACKGROUND Combination antifungal therapy (amphotericin B deoxycholate and flucytosine) is the recommended treatment for cryptococcal meningitis but has not been shown to reduce mortality, as compared with amphotericin B alone. We performed a randomized, controlled trial to determine whether combining flucytosine or high-dose fluconazole with high-dose amphotericin B improved survival at 14 and 70 days. METHODS We conducted a randomized, three-group, open-label trial of induction therapy for cryptococcal men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
370
6
15

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(417 citation statements)
references
References 23 publications
8
370
6
15
Order By: Relevance
“…One of the primary drawbacks of polyenes is their significant toxicity, although the development of lipid formulations of amphotericin B has reduced this problem significantly (Hamill 2013); such formulations are quite expensive and not available in some regions. Amphotericin B, in combination with the adjunctive drug 5-flucytosine, is the treatment of choice for cryptococcal meningitis (Day et al 2013) as well as for awide range of less common invasive mycoses. For many of the most common invasive fungal infections, the better tolerated azoles and echinocandins have emerged as first-line agents.…”
Section: Current Antifungal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the primary drawbacks of polyenes is their significant toxicity, although the development of lipid formulations of amphotericin B has reduced this problem significantly (Hamill 2013); such formulations are quite expensive and not available in some regions. Amphotericin B, in combination with the adjunctive drug 5-flucytosine, is the treatment of choice for cryptococcal meningitis (Day et al 2013) as well as for awide range of less common invasive mycoses. For many of the most common invasive fungal infections, the better tolerated azoles and echinocandins have emerged as first-line agents.…”
Section: Current Antifungal Therapiesmentioning
confidence: 99%
“…In part, this enthusiasm is based on the shown therapeutic superiority of coadministering amphotericin B and 5-flucytosine (5-FC) to treat cryptococcal meningitis (Day et al 2013). It is further based on the extensive network of synthetic lethal genetic interactions identified between loss-of-function (or hypomorphic) mutations otherwise singly tolerated by S. cerevisiae (Costanzo et al 2010).…”
Section: Antifungal Drug Discovery: Process and New Approachesmentioning
confidence: 99%
“…nie dorównuje skutecznością terapii skojarzonej amfoterycyną i flucytozyną [17][18][19][20]. Najmniej skuteczna jest monoterapia flukonazolem -stwierdzono o 30% wyższą śmier-telność w 10. tygodniu leczenia w porównaniu z leczeniem opartym na amfoterycynie [21].…”
Section: Leczenie CMunclassified
“…The use of the most rapidly fungicidal combinations in the induction phase of treatment (at least 2 wk, and longer in the immunocompetent host and/ or C gattii infection) is thus recommended for any patient with CNS disease. The combination of AmBd (0.7 -1.0 mg/kg/d) and 5FC (25 mg/ kg four times a day) sterilizes the CSF most rapidly (van der Horst et al 1997;Brouwer et al 2004;Day et al 2013), and showed long-term survival benefit in a recent phase III trial (Day et al 2013). The use of adjunctive interferon (IFN)-g with AmBd and 5FC leads to even faster rates of clearance and can be considered in refractory cases (Perfect et al 2010;Jarvis et al 2012).…”
Section: Clear the Fungus Rapidlymentioning
confidence: 99%
“…In organ transplant recipients on concomitant nephrotoxic drugs, liposomal AmB (3 -4 mg/kg/d) should be substituted for the deoxycholate preparation (Perfect et al 2010). Where 5FC is not available, fluconazole 800 -1200 mg/d can be combined with AmBd (Pappas et al 2009;Loyse et al 2012;Day et al 2013). Where AmBd cannot be safely administered for 14 d, alternatives include shorter (5 -7 d) courses (Muzoora et al 2012) or the oral combination of fluconazole 1200 mg/d plus 5FC (Nussbaum et al 2010), currently undergoing phase III randomized controlled trials in Africa (see www.…”
Section: Clear the Fungus Rapidlymentioning
confidence: 99%